The Natural Science Museum goes to School - Scur, Luciana; Scopel, Janete Maria; Vons, Paula Cristina de Oliveira (Scientia cum Industria, 2016)
Currently it is proven the need to stimulate actions that modify the behavior of human beings in relation to nature. Schools and non-formal education spaces contribute to citizens to develop values, attitudes and responsibilities facing the environment in which they live. The non-formal educational environments provide teaching resources, teaching and different methodologies that complement the actions of formal education. Expanding its environmental education activities, the Museum of Natural Sciences of the University of Caxias do Sul, since 2013, has been developing the project "The Natural Science Museum Goes to School", in order to awaken the scientific spirit, spreading knowledge aimed at preservation of natural resources, contributing to the enrichment of science education, stimulating the development of educational activities with the support of partner schools in the region. Initially, students and teachers visit the Museum of Natural Sciences and then are developed workshops, lectures and recreational activities in schools, integrating these education spaces. Teachers also develop activities with students, integrating knowledge to partner with those seen in the classroom. Finally, this knowledge is presented through a show of open jobs to the community. During the years 2013 and 2014 the project reached about 1,100 students and by integrating museum and school was provided to these differentiated learning, where knowledge of the interrelationships between natural resources and the living beings was built in an interdisciplinary way, highlighting the museums as important teaching and learning in science sites. http://dx.doi.org/10.18226/23185279.v3iss3p123